Productivity and Play in Organizations: Executive Perspectives on the Real-World Organizational Value of Immersive Virtual Environments. Issue 2 (1st June 2008) - Hansen, Sean; Berente, Nicholas; Pike, Jacqueline; Bateman, Patrick J.
In exploring the productive potential of virtual worlds, one relevant line of inquiry is the degree to which immersive online environments can support the objectives of real-world enterprises. Despite the favorable treatment of virtual worlds in the popular and business press, organizations remain cautious in their acceptance and adoption of virtual environments. Since there is a dearth of academic literature on this facet of the virtual world phenomenon, this research aims to provide an assessment of executive perspectives on the potential impact of virtual worlds on businesses and the challenges that may be encountered in organizational application of such environments. To capture business-oriented perceptions of virtual worlds we analyzed, the reports of twenty-five business executives who recently spent considerable time training in and exploring Second Life, a popular online virtual environment. We identify and discuss seven tensions reflected in their assessment of the organizational role of virtual worlds, and situate these tensions in the prevailing computer-mediated communication discourse. Findings point to significant parallels with evaluative perspectives on earlier waves of Internet-based innovation, insights from the existing literature on computer-mediated communication, and an opportunity for theory generation through dialectical reasoning.